DESIGN AND SCREENING OF GALLIC ACID DERIVATIVES AS INHIBITORS OF MALARIAL DIHYDROFOLATE REDUCTASE (DHFR) BY IN SILICO DOCKING - Ade Arsianti; Astuty, Hendri; Fadilah; Bahtiar, Anton; Tanimoto, Hiroki; Kakiuchi, Kiyomi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Malaria is an infection disease caused by plasmodium parasite with high prevalence in tropic and subtropic countries. The aim of this work was to design and screening of gallic acid derivatives as inhibitors of malarial dihydrofolate reductase (DHFR) by in silico docking. Methods: The derivatives were designed by expanding the carboxyl group of gallic acid with open-chain moiety of L-threonine-allyl esters, as well as to modify the hydroxy groups on the aromatic ring of gallic acid with methoxyl group in the derivatives. In silico approach has been utilized in finding the potential antimalaria of gallic acid derivatives. Fourteen Gallic acid derivatives (compound 2-15) were modeled into 3D structures by ACD Labs software. Geometry optimization and minimization of energy 3D structure of gallic acid derivatives as ligands using the MOE software. Docking process and amino acid analysis were executed by using MOE software. Results: In silico docking study resulted in the three top-ranked compounds, namely compound 5, 8 and 12. Among those three top-ranked compounds, compound 12 (octyl gallate), exhibited the strongest interaction and greatest inhibitory activity against the receptor of malarial DHFR. Conclusion Our results clearly demonstrated that compound 12 (octyl gallate) could be developed as a promising candidate for the new anti-malarial agent.